Studi Korelasi antara Motivasi Kerja, Kompetensi Profesional Guru, dan Etos Kerja terhadap Kinerja Guru - Segantara, I Gede Mahendra; Yudana, I Made; Sunu, I Gusti Ketut Arya (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2017)
The study was conducted in order to figure out and analyze the correlation coefficient between (1) work motivation and the teachers’ performances at SMP Negeri 2 Bebandem; (2) teachers’ professional competencies and the teachers’ performances at SMP Negeri 2 Bebandem; (3) work morale and the teachers’ performances at  SMP Negeri 2 Bebandem; (4) work motivation, teachers’ professional competencies, and work morale toward the teachers’ performances at SMP Negeri 2 Bebandem.The study utilized an ex-post facto design, while the data were collected by using questionnaires ofachieving motivation, teachers’ professional competencies, and work morale, as well as the teachers’ performances. The data were analyzed by multiple regressions and correlation test. The population of the study is 43 teachers of SMP Negeri 2 Bebandem. Based on the findings that the variables of work motivation, teachers’ professional competencies, as well as work morale could become predictors to improve the teachers’ performances.